Insights from a cluster of tuberculosis outbreak in a psychiatric hospital—Shandong Province, 2024 - Shulei Wang; Peilin Diao; Jingyu Liu; Shiwen Wang; Yuelei Wang; Xiaomin He (Infectious Medicine)
Background: This study analyzes the epidemiological characteristics, investigation, and management of a tuberculosis (TB) outbreak in July 2024 at a psychiatric hospital in Yantai City, Shandong Province. It aims to provide recommendations for the prevention and control of TB in high-risk settings, such as psychiatric hospitals. Methods: An epidemiological investigation was conducted, involving case analyses, symptom screenings, tuberculin skin tests (TST), chest X-rays (CXR), and an evaluation of the outbreak's progression and findings. Results: Four active pulmonary TB cases were confirmed between July 3 and July 12, 2024. Among 313 contacts screened, 37 tested positive, with healthcare workers showing a higher positivity rate (18.60 %) compared with patients with mental illnesses (9.05 %). Healthcare workers’ close contacts had significantly higher positivity rates than their casual contacts. Conclusions: The primary cause of this cluster outbreak was delayed outbreak alerts following the identification of the index case. To enhance outbreak prevention, medical institutions should clarify whether TB patients with a history of mental illness have been admitted in psychiatric hospitals and, if so, initiate timely outbreak alerts. Additionally, psychiatric hospitals should improve healthcare worker training to recognize TB symptoms and promptly report cases involving patients with mental illnesses.